Distributed high-efficiency entropy energy-saving clustering routing algorithm for SDWSN - Qiaoqiao MA; Ligang DONG; Xian JIANG (Dianxin kexue)
In order to improve the life of software defined wireless sensor network (SDWSN) and reduce the energy consumption of data transmission, a hybrid optimization algorithm based on firefly algorithm (FA) and biogeography-based optimization (BBO) were designed, and based on the hybrid optimization algorithm, a distributed high-efficiency entropy energy-saving clustering routing algorithm (DHEEC) was designed, using energy entropy and hybrid optimization algorithm for cluster head selection.The simulation results show that the hybrid optimization algorithm outperforms other algorithms on standard functions.The number of death rounds of 10% nodes of DHEEC is about 13.89% higher than that of IFCEER, and about 41.05% higher than that of DEEC-FA, and the energy utilization is improved.